Getting the knack for team-improvised adaptation: The role of reflexivity and team mental model similarity - Abrantes, A.; Passos, A. M.; Cunha, M. P.; Santos, C. M. (Journal of Applied Behavioral Science, 2022)
Organizational teams operate in increasingly volatile environments in which the speed and degree of change accelerates, demanding rapid adaptation processes namely of the improvisational type. It is therefore essential to understand how to prepare teams to operate in such contexts. This work investigates the effects of team mental model similarity, in-action reflexivity, and transitional reflexivity on team-improvised adaptation performance and on team-improvised adaptation learning. Two experiments were conducted with a total of 121 teams. We manipulated the independent variables and used an overtime design to measure team-improvised adaptation learning. Our findings suggest that teams operating in unpredictable environments that require rapid adaptation should be able to reflect collectively, both while acting and between tasks. These teams should also develop a common understanding of the main elements of the context and the task, so that they are effective in the face of unpredictability and rapid change.